Instrumented Field Performance of Vertical Reinforced Earth Wall - Ali, Faisal; Kim Huat, Bujang (Universiti Putra Malaysia Press, 1993)
This paper presents the site observation and results of full-scale investigations of a section of an earth retaining wall constructed at Bangsar, Kuala Lumpur. The studies involved instrumenting 24 reinforcing strips with 98 strain gauges and installation of an inclinometer casing. Two pull out tests were also performed to determine the apparent friction coefficient. The performance of the reinforced earth wall was monitored and analysed. Field observations on maximum tensile forces in reinforcing strips at the end of construction were in reasonably good agreement with theoretical values. No appreciable horizontal movement was detected during the first three and a half months after construction.